(untitled) (Journal of Medical Sciences, 2021)
Conventional cardiovascular risk factors such as smoking, hypertension, hypercholesterolemia and diabetes have been the primary concerns in cardiovascular disease treatment and prevention programmes, with limited interest in obesity. This study aims to evaluate different anthropometric parameters and their relationship to some risk factors for cardiovascular disease in a sample of adult men. The study was conducted on 120 random samples of men at Al-Barrak General Hospital and the reference laboratory in Sebha city, aged 23 years and over. Some data on these subjects were taken in a questionnaire, and anthropometrics (weight, height, waist circumference, and hip circumference), BMI, waist/hip circumference WHpR and waist circumference/height WHtR were calculated. The prevalence of eight risk factors for cardiovascular disease (hypertension, diabetes, high total cholesterol, triglycerides, low-density lipoprotein (LDL), and reduced high-density lipoprotein (HDL), high atherosclerotic index (AI), and smoking) was studied. The prevalence of obesity among the study sample using body mass index was 27.5%, while according to waist circumference, waist circumference/hip rate and waist circumference/height rate, they were as follows: (51.3%, 12.5%, 72.5%), respectively). Waist circumference/height, WHtR, increased the prevalence of most cardiac risk factors at significant levels p < 0.05, while body mass index (BMI) was associated with diabetes, high triglycerides, and arterial hypertension. Hardness index at significant levels p < 0.05. This study concluded that central obesity indices, specifically waist circumference/height (WHtR), were more important than body mass index (BMI) in determining obesity rate, and were more likely to be associated with cardiovascular disease risk factors in adult men.